Fouling mechanisms in anoxic-aerobic sequencing batch membrane bioreactor based on adapted Hermia models and main foulant characteristics. (1st December 2022) - Shams, Hossein; Alavi Moghaddam, Mohammad Reza; Maknoon, Reza; Mąkinia, Jacek; Hasani Zonoozi, Maryam
Abstract: Various derivatives of Hermia models (complete pore blocking, intermediate pore blocking, cake layer formation, and standard pore blocking) and different assessments of foulant characteristics have long been used to determine the membrane fouling mechanisms. Accordingly, this study aims to adapt Hermia models and their combination according to the operating conditions of an anoxic-aerobic sequencing batch membrane bioreactor (A/O-SBMBR). In addition, fouling mechanisms of the A/O-SBMBR were assessed using these models along with the main foulant characteristics. Models fitting with the transmembrane pressure (TMP) data indicated that the intermediate-standard model was accounting for the increased fouling during the whole regular operating period, with the residual sum of squares (RSS) of 58.3. A more detailed study on the distinct stages of TMP curve showed that the intermediate-standard model had the best fit in stages of 2 and 3, with the RSS equal to 2.6 and 2.8, respectively. Also, the complete-standard model provided the best description of the fouling mechanism in stage 4, with the RSS of 12.5. Different analyzes revealed how the main foulant characteristics affect the occurrence of intermediate, complete and standard fouling mechanisms in the A/O-SBMBR, which is consistent with the fitting results of the adapted Hermia models. The modeling and experimental methods used in the presented study provided a valuable basis to prevent and control membrane fouling in membrane bioreactors. Graphical abstract: Image 1 Highlights: Hermia models were adapted for the membrane bioreactor operating conditions. Fouling mechanisms were assessed through the adapted models/foulant characteristics. The standard-intermediate/standard-complete were the dominant fouling mechanisms. Fitting adapted models in distinct stages provided a better fouling description. The conformity between the adapted models/foulant characteristics was investigated.